Indo-Pacific Geopolitical Dynamics: The Role of Australia, AUKUS, and Increasing the Defense Budget - R, Andana Prawitra; Perwita, Anak Agung Banyu; Inkiriwang, Frega Ferdinand Wenas (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of the defense and security situation in the Indo-Pacific region due to the situation in the South China Sea made the US alert and established an AUKUS defense pact. AUKUS has members from the US, UK and Australia. Australia, as a country located closer to the South China Sea, is the focus of the other two AUKUS members in countering Chinese hegemony. The purpose of this article is to find out how Australia is trying to build its defense industry by increasing the defense budget when joining AUKUS. This research was conducted using qualitative descriptive methods. The data used is secondary data originating from published journals and reports. This research concludes that Australia's joining AUKUS made Australia try to equalize its military capabilities with the US and UK by increasing its defense budget.